Endocytosis of synaptic vesicle membrane at the frog neuromuscular junction (The Rockefeller University Press, 1984)
Frog nerve-muscle preparations were quick-frozen at various times after a single electrical stimulus in the presence of 4-aminopyridine (4-AP), after which motor nerve terminals were visualized by freeze-fracture. Previous studies have shown that such stimulation causes prompt discharge of 3,000-6,000 synaptic vesicles from each nerve terminal and, as a result, adds a large amount of synaptic vesicle membrane to its plasmalemma. In the current experiments, we sought to visualize the endocytic retrieval of this vesicle membrane back into the terminal, during the interval between 1 s and 2 min after stimulation. Two distinct types of endocytosis were observed. The first appeared to be rapid and nonselective. Within the first few seconds after stimulation, relatively large vacuoles (approximately 0.1 micron) pinched off from the plasma membrane, both near to and far away from the active zones. Previous thin-section studies have shown that such vacuoles are not coated with clathrin at any stage during their formation. The second endocytic process was slower and appeared to be selective, because it internalized large intramembrane particles. This process was manifest first by the formation of relatively small (approximately 0.05 micron) indentations in the plasma membrane, which occurred everywhere except at the active zones. These indentations first appeared at 1 s, reached a peak abundance of 5.5/micron2 by 30 s after the stimulus, and disappeared almost completely by 90 s. Previous thin-section studies indicate that these indentations correspond to clathrin-coated pits. Their total abundance is comparable with the number of vesicles that were discharged initially. These endocytic structures could be classified into four intermediate forms, whose relative abundance over time suggests that, at this type of nerve terminal, endocytosis of coated vesicles has the following characteristics: (a) the single endocytotic event is short lived relative to the time scale of two minutes; (b) earlier forms last longer than later forms; and (c) a single event spends a smaller portion of its lifetime in the flat configuration soon after the stimulus than it does later on.